Między zachodnim kolonializmem a wschodnim imperializmem. Dyskurs postkolonialny a trajektoria rozwojowa społeczeństw Europy Środkowo-Wschodniej w świetle nie-Marksowskiego materializmu historycznego - Brzechczyn, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The purpose of this paper is to discuss a problem of applicability of postcolonial studies/postcolonial perspective to history of Polish society and wider — East Central Europe, especially in the 19th and 20th centuries. In the first part, the main standpoints in Polish discussion are identified and the certain attempt of an application of categories of postcolonial studies are critically analyzed and discussed. Furthermore, in part two, the typology of social dominations (political, economic and cultural and variants of external subordinations) based on non-Marxian historical materialism is constructed in order in the chapter fourth to interpret the developmental trajectory of East-Central European societies. In the light of the presented interpretation, the ‘resolving ability’ of postcolonial perspective is too weak to be applied without essential modification to the history of societies living in this region of Europe, where the mosaic of different configurations of class domination shaped and evolved.
Keywords: totalitaryzm; imperializm; Europa Środkowa; postkolonializm; posttotalitaryzm; komunizm; kolonializm; nie-Marksowski materializm historyczny